Assessing the effects of Queuing Algorithms and Routing Protocols on Quality of Service for Video Traffic over IPv4 and IPv6 networks.1 - S. Mresa, Elfurjani; S. Ergheegh, Abdelfattah (Libyan Journal of Science &Technology, 2026)
This paper investigates the impact of two widely used routing protocols—Open Shortest Path First (OSPF) and Enhanced Interior Gateway Routing Protocol (EIGRP)—and two queueing tech niques—Priority Queuing (PQ) and Weighted Fair Queuing (WFQ)—on the Quality of Service (QoS) of video conferencing traffic in both IPv4 and IPv6 networks. Through extensive simula tions, we evaluate the performance of each queueing method in combination with each routing protocol under conditions of heavy traffic and moderately large network topologies. The analysis focuses on key QoS parameters, including throughput, end-to-end delay, packet delay variation, packet loss, and point-to-point delay. The objective is to identify the optimal pairing of routing protocol and queueing mechanism that yields the best QoS performance for video traffic in TCP/IP environments. Furthermore, the scalability of the results is assessed by replicating the scenarios in IPv6 networks. All simulations were conducted using OPNET Modeler 14.5A, provid ing a comprehensive evaluation of the interactions between routing protocols and queueing dis ciplines across diverse network conditions.